2009
DOI: 10.1590/s1413-70542009000700022
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo inicial in vitro de gemas axilares de Ananas comosus (L.) Merr., em meio líquido/sólido, na presença/ausência de luz

Abstract: COMUNICAÇÃO CULTIVO INICIAL IN VITRO DE GEMAS AXILARES DE RESUMOA capacidade regenerativa de gemas axilares de abacaxizeiro cv. Pérola (Ananas comosus (L.) Merr.) foi avaliada em meio de cultivo líquido e gelificado, na presença e ausência de luz, com o objetivo de produzir material para subsequentes fases da micropropagação. Os explantes foram estabelecidos, por 60 dias, em meio MS acrescido de 0,63 M de ANA e 2,5 M de BAP. O delineamento experimental foi inteiramente casualizado, constituído com quatro trata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to Karasawa et al (2002), in tissue culture, the physical state of the culture medium has a fundamental effect on the morphogenesis and growth of the shoots, which can cause serious problems in the development of explants. However, other authors report that liquid medium could successfully be adopted for multiplication of potato seedlings Fortes, 2003, 2004), banana (de Siqueira et al, 2013), and pineapple (Barboza et al, 2009). Regarding the successful generation of autopolyploid plants, Allum et al (2007) reported that the combination of high antimitotic doses and long exposure times can double the DNA content, resulting in high ploidy levels and the generation of several mixoploids.…”
Section: Effect Of Oryzalin Concentration and Exposure Time On Cassavmentioning
confidence: 99%
“…According to Karasawa et al (2002), in tissue culture, the physical state of the culture medium has a fundamental effect on the morphogenesis and growth of the shoots, which can cause serious problems in the development of explants. However, other authors report that liquid medium could successfully be adopted for multiplication of potato seedlings Fortes, 2003, 2004), banana (de Siqueira et al, 2013), and pineapple (Barboza et al, 2009). Regarding the successful generation of autopolyploid plants, Allum et al (2007) reported that the combination of high antimitotic doses and long exposure times can double the DNA content, resulting in high ploidy levels and the generation of several mixoploids.…”
Section: Effect Of Oryzalin Concentration and Exposure Time On Cassavmentioning
confidence: 99%
“…Micropropagation protocols of pineapple have been developed and adjusted since the work of Aghion & Beauchesne (1960). From then many studies have demonstrated the applicability of this technique to the programs of pineapple genetic improvement, as well as for commercial production of plantlets (BE & DEBERGH, 2006;SOUZA et al, 2009;BARBOZA et al, 2009;AL-SAIF et al, 2011;ZURAIDA et al, 2011; SCHERER USMAN et al, 2013;FARAHANI, 2014;NELSON et al, 2015;SCHERER et al, 2015ab;OLIVEIRA-CAUDURO et al, 2016;SILVA et al, 2016;MENDONÇA, et al, 2017). C u r r e n t l y, c o n v e n t i o n a l t e c h n i q u e s o f micropropagation have been routinely used in the process of multiplication of new hybrids by research institutions, even though the protocols must be adjusted for each new variety.…”
Section: By Micropropagationmentioning
confidence: 99%